Analisis Retorika Etos, Patos, dan Logos dalam Dakwah Panji Gumilang - Haryadie, Yan (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2023)
Panji Gumilang, as a widely known and controversial da'wah figure, shows a unique rhetorical ability in conveying his religious messages. Ethos is built through the image of an intellectual cleric and leader of a modern Islamic boarding school. Pathos is manifested through a narrative of unity, national symbolism, and emotional language that arouses the audience. Meanwhile, logos is seen from the delivery of rational and contextual arguments related to Islamic issues, education, and nationality. Although his rhetorical strategy is effective in influencing listeners, he is not free from controversy because of his interpretation of religion that differs from the mainstream. This study shows that the success of rhetoric is greatly influenced by the speaker's ability to combine credibility, emotion, and logic in a balanced way. Keywords : rhetoric, ethos, pathos, logos, Panji Gumilang, da'wah, communication.